Differently Pre-treated Rapeseed Meals Affect in vitro Swine Gut Microbiota Composition - Long, Cheng; de Vries, Sonja; Venema, Koen (Frontiers in Microbiology, 2020)
The aim of the study was to investigate the effect of untreated and processed rapeseed meal (RSM) on fibre degradability by pig gut microbiota and the adaptation of the microbiota to the substrate, by using the Swine Large Intestine in vitro Model (SLIM). A standardized swine gut microbiota was fed for 48 h with pre-digested RSM which was processed enzymatically by a cellulase (CELL), two pectinases (PECT), or chemically by an alkaline (ALK) treatment. Amplicons of the V3-V4 region of the 16S rRNA gene were sequenced to evaluate the gut microbiota composition, whereas short chain fatty acids (SCFA) were measured to assess fibre degradation. Adaptive gPCA showed that CELL and ALK had larger effects on the microbiota composition than PECT1 and PECT2, and all substrates had larger effects than CON. The relative abundance of family Prevotellaceae was significantly higher in CELL treatment compared to others. Regardless of the treatments (including CON), the relative abundance of Dorea, Allisonella, and FamilyXIIIUCG_001 (in the order of Clostridiales) were significantly increased after 24 h, and Parabacteroides, Mogibacterium, Intestinimonas, Oscillibacter, RuminococcaceaeUCG_009, Acidaminococcus, Sutterella, and Citrobacter were significantly higher in abundance at time point 48 compared to the earlier time points. Prevotella 9 had significant positive correlations with propionic and valeric acid, and Mogibacterium positively correlated with acetic and caproic acid. There was no significant difference in SCFA production between untreated and processed RSM. Overall, degradability in the processed RSM was not improved compared to CON during the RSM adaptation period. However, the significantly different microbes detected among treatments, and the bacteria considerably correlating with SCFA production might be important findings to determine strategies to shorten the fibre adaptation period of the microbiota, in order to increase feed efficiency in the animal, and particularly in pig production.